2012
DOI: 10.4141/cjps2011-220
|View full text |Cite
|
Sign up to set email alerts
|

Response of dry beans to halosulfuron applied postemergence

Abstract: Soltani, N., Shropshire, C. and Sikkema, P. H. 2012. Response of dry beans to halosulfuron applied postemergence. Can. J. Plant Sci. 92: 723–728. Four field trials were conducted over a 2-yr period (2009 and 2010) at Exeter and Ridgetown, Ontario, to evaluate the tolerance of adzuki, black, cranberry, kidney, otebo, pinto, Small Red Mexican and white beans to halosulfuron applied postemergence (POST) at 35 and 70 g a.i. ha−1. All treatments including the non-treated control were maintained weed free during the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 16 publications
2
23
1
1
Order By: Relevance
“…Trifluralin, s-metolachlor, halosulfuron, and imazethapyr applied alone or in combination applied PPI caused 4% or less visible injury 1 and 4 weeks after emergence (WAE) in white bean (Table 1). This is similar to other studies that have shown up to 6% injury in white bean with halosulfuron applied alone or in tankmixes with other herbicides [9][10][11]. Silvey et al [12] also found minimal and transient injury (5%) with halosulfuron in snap bean.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Trifluralin, s-metolachlor, halosulfuron, and imazethapyr applied alone or in combination applied PPI caused 4% or less visible injury 1 and 4 weeks after emergence (WAE) in white bean (Table 1). This is similar to other studies that have shown up to 6% injury in white bean with halosulfuron applied alone or in tankmixes with other herbicides [9][10][11]. Silvey et al [12] also found minimal and transient injury (5%) with halosulfuron in snap bean.…”
Section: Resultssupporting
confidence: 86%
“…Silvey et al [12] also found minimal and transient injury (5%) with halosulfuron in snap bean. In other studies, halosulfuron reduced yield of white bean as much as 9% and adzuki bean as much as 68% but had no effect on the seed yield of black, cranberry, kidney, otebo, pinto, and small red Mexican beans [9,10]. In another study halosulfuron applied postemergence reduced seed yield of white bean as much as 21% [11].…”
Section: Resultsmentioning
confidence: 83%
“…halosulfuron-methyl applied POST in Phaseolus vulgaris have found up to 50% injury in white bean [12] but no adverse effect on seed yield of black, cranberry, kidney, otebo, pinto and small red Mexican beans [15].…”
Section: Halosulfuron-methylmentioning
confidence: 97%
“…In previous studies, it has been reported that halosulfuron, applied PPI, is safe for use on most market classes of dry beans with the exception of adzuki, mung, and snap bean (Silvey et al 2006;Soltani et al 2009Soltani et al , 2013aStewart et al 2010). Halosulfuron, applied PPI, caused 58 to 70% injury in adzuki bean and reduced adzuki bean height 52 to 70% (Soltani et al 2009(Soltani et al , 2012aStewart et al 2010). Silvey et al (2006) reported that halosulfuron applied PRE, POST, and PRE follow by POST caused 4, 8, and 5% injury in snap bean and reduced snap bean yield 11, 7, and 15%, respectively.…”
Section: Crop Injurymentioning
confidence: 99%